Preparation method of photo-curing oxygen-producing silk fibroin hydrogel and hydrogel

The preparation of oxygen-producing fibroprotein hydrogels through photocuring technology has solved the problems of poor biocompatibility and numerous operating steps of existing oxygen sustained-release hydrogels, achieving a good biocompatible oxygen sustained-release effect and a simple production process.

CN119499433APending Publication Date: 2025-02-25WUHAN TEXTILE UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411422377.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing oxygen sustained-release hydrogels have poor biocompatibility and numerous operating steps, which affects their application in the medical field.

Method used

The preparation steps are simplified by photocuring technology by mixing riboflavin solution with silk fibroprotein solution, adding peroxide, and crosslinking under ultraviolet lamp irradiation.

Benefits of technology

It has achieved a high biocompatible oxygen sustained-release hydrogel, simplified operation steps and high production efficiency. The hydrogel has good adhesion and wet mechanical properties, and is suitable for wound healing and scar repair.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119499433A_ABST
    Figure CN119499433A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps: adding a riboflavin solution into a silk fibroin solution, stirring and mixing to obtain a mixed solution, adding peroxide into the mixed solution, stirring at a constant temperature to obtain a suspension liquid, putting the suspension liquid into a light-transmitting mold, and carrying out vacuum drying to obtain the light-cured oxygen-producing silk fibroin hydrogel. The suspension liquid in the mold is irradiated by an ultraviolet lamp, and when the suspension liquid is in a gel state, the photo-curing oxygen-producing silk fibroin hydrogel can be obtained. According to the design, oxygen can be slowly released, the material is good in biocompatibility, green, environmentally friendly and free of pollution, and meanwhile operation steps are simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an oxygen-releasing hydrogel, belonging to the technical field of light-cured oxygen-generating materials, and in particular to a preparation method of a light-cured oxygen-generating silk fibroin hydrogel and the hydrogel. Background Art

[0002] Oxygen plays an important role in promoting inflammatory response, scar repair, fracture and nerve repair. As an energy source, it supports the activation and proliferation of immune cells, accelerates the inflammatory treatment process, and promotes collagen synthesis and fibrosis, accelerating scar maturation and stabilization. Especially in the process of fracture repair and nerve repair, oxygen provides energy support for the growth and differentiation of bone cells and nerve cells, and regulates the expression of nerve growth factor to achieve the repair effect.

[0003] At the same time, silk fibroin hydrogel has good biocompatibility and is widely used in the medical field. It is mainly used to prepare biomedical materials such as artificial skin, artificial blood vessels and tissue engineering scaffolds. It can reduce immune and rejection reactions and promote wound healing and regeneration.

[0004] The invention patent application with application number 202211209875.3 and application date September 30, 2022 discloses an oxygen slow-release hydrogel and its preparation method and application, which includes the following steps: firstly, peroxide, photoinitiator and methacrylated gelatin solution are mixed to make the peroxide evenly dispersed in the hydrogel substrate solution, and ultraviolet cross-linking is adopted to obtain a hydrogel material; then, the obtained hydrogel material is immersed in an epigallocatechin gallate solution for not less than 2 hours, and then rinsed to obtain an oxygen slow-release hydrogel. Although the hydrogel prepared by this design has the function of oxygen slow release, it has the following defects: First, the main raw material of this design is methacrylated gelatin solution, which is a toxic substance that can harm the human body and has poor biocompatibility; Secondly, the design first requires mixing peroxide, photoinitiator, and methacrylated gelatin solution, then UV cross-linking, and then immersion in epigallocatechin gallate solution, and finally rinsing, which involves many operating steps.

[0005] The information disclosed in this background technology section is only intended to increase the understanding of the overall background of the application, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art already known to ordinary technicians in this field. Summary of the invention

[0006] The purpose of the present invention is to overcome the defects and problems of poor biocompatibility and more operating steps in the prior art, and to provide a method for preparing a light-cured oxygen-generating silk fibroin hydrogel and a hydrogel with better biocompatibility and fewer operating steps.

[0007] To achieve the above objectives, the technical solution of the present invention is: a method for preparing a light-cured oxygen-generating silk fibroin hydrogel, the preparation method comprising the following steps: The first step: firstly, adding the riboflavin solution into the silk fibroin solution and stirring to obtain a mixed solution, and then adding peroxide into the mixed solution and stirring at a constant temperature to obtain a suspension; Step 2: first place the suspension in a light-transmitting mold, and then irradiate the suspension in the mold with ultraviolet light. When the suspension changes from clear to translucent gel, light-cured oxygen-generating silk fibroin hydrogel can be obtained.

[0008] In the second step, the ultraviolet lamp irradiation time is 1-30 minutes.

[0009] In the first step, the mass percentage concentration of the silk fibroin solution is 2%-8%, the concentration of the riboflavin solution is 0.01-0.5 mM / L, and the volume ratio between the silk fibroin solution and the riboflavin solution is 100:1-50:1.

[0010] In the first step, the mass of the peroxide is 0.3%-3.0% of the mass of the mixed solution.

[0011] The peroxide is benzoyl peroxide, calcium peroxide or any mixture of the two.

[0012] In the first step, the constant temperature stirring means that after adding peroxide to the mixed solution, constant temperature stirring is performed under a magnetic heating stirrer at a temperature of 25-70° C. for 5-35 minutes.

[0013] In the first step, the silk fibroin solution is prepared according to the following steps: First, degummed silk is obtained, cut into pieces, and then placed in a lithium bromide solution, and then dissolved in a water bath at a temperature of 20-65°C, and then dialyzed for 48-72 hours, and then centrifuged to obtain a silk fibroin solution; The concentration of the lithium bromide solution is 5-15 mol / L, and the mass volume ratio of the degummed silk to the lithium bromide solution is 1:2kg-1:10L.

[0014] The degummed silk is prepared according to the following steps: First, the raw silk is placed in a container containing deionized water, and anhydrous sodium carbonate is added for the first time, and then heated while stirring until boiling for 15-45 minutes, then the silk is taken out for washing, and then the washed silk is added to a container containing deionized water, and anhydrous sodium carbonate is added for the second time, and then heated while stirring until boiling for 15-45 minutes, then the silk is taken out for washing, and then the washed silk is added to a container containing deionized water, and anhydrous sodium carbonate is added for the third time, and then heated while stirring until boiling for 15-45 minutes, then the silk is taken out for washing, and then dried to obtain degummed silk; The mass of anhydrous sodium carbonate added for the first and second times is greater than the mass of anhydrous sodium carbonate added for the third time.

[0015] During the first, second and third stirring and heating, the mass ratio of silk to deionized water was in the range of 1:10-1:100 each time. Meanwhile, after adding anhydrous sodium carbonate each time, the mass percentage concentration of sodium carbonate was in the range of 0.01-0.5%.

[0016] A hydrogel is prepared according to the preparation method of the light-cured oxygen-generating silk fibroin hydrogel.

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. In the preparation method of a light-cured oxygen-generating silk fibroin hydrogel and the hydrogel of the present invention, a riboflavin solution is first added to a silk fibroin solution and stirred to obtain a mixed solution, and then peroxide is added to the mixed solution and stirred at a constant temperature to obtain a suspension, and then the suspension is placed in a light-transmitting mold, and then the suspension in the mold is irradiated with an ultraviolet lamp. When the suspension changes from clear to translucent colloid, a light-cured oxygen-generating silk fibroin hydrogel can be obtained. The advantages of this design include: First point: In this design, silk fibroin is the main component of hydrogel, riboflavin is the photoinitiator, and peroxide can act as an oxidant to catalyze the reaction efficiently, promote the rapid cross-linking of hydrogel, and at the same time, it can act as an oxygen releaser to release oxygen, which helps to inhibit the formation of scars and achieve the effect of repairing blood vessels and wound healing; Second point: This product is a three-dimensional mesh gel structure, which can act as a physical barrier to limit the rapid diffusion and release of oxygen. Moreover, the silk fibroin hydrogel has a mesh pore structure. The smaller pore structure combined with the tighter mesh structure can slow down the release of oxygen. In addition, as the hydrogel is degraded by the wound tissue fluid, the peroxide gradually emerges and gradually releases oxygen, which is also a slow-release effect. The combination of the triple slow-release effect can achieve the effect of slow-release oxygen as a whole, and then prepare a hydrogel medical polymer dressing that can release oxygen for a long time. Third point: Since peroxides, such as calcium peroxide, are hydrophilic, and the silk fibroin solution contains a large amount of water, peroxides can easily obtain a high degree of mixing uniformity in the silk fibroin solution. At the same time, the cross-linked silk hydrogel has a three-dimensional grid structure, which is conducive to the high uniformity of mixing effect before extension, so that calcium peroxide can be evenly distributed on the surface of the hydrogel and its internal structure, thereby improving the subsequent oxygen release effect. Fourth point: The main raw materials of this design are silk fibroin, riboflavin, and peroxide. Among them, silk fibroin comes from mulberry silk and has good biocompatibility and degradability. Riboflavin also has good biocompatibility and is easy to degrade. Peroxide is basically consumed in the gel process, and its content is negligible and non-toxic, so that the final hydrogel is non-toxic and harmless, degradable, and the degradation product is non-toxic and harmless. It is green, environmentally friendly, pollution-free, and low-cost, and can be widely used in medical fields such as wound infection and repair; Fifth point: This design only requires mixing three raw materials and then irradiating with ultraviolet light. Not only does it have fewer steps, it is also easy to operate and takes less time overall. Therefore, the present invention can not only slowly release oxygen and has fewer operation steps, but also has good biocompatibility and is green, environmentally friendly and pollution-free.

[0018] 2. In the preparation method and hydrogel of a photocurable oxygen-generating silk fibroin hydrogel of the present invention, the peroxide used not only plays the role of cross-linking the silk fibroin solution to form a gel in the early stage, but also acts as an oxygen release agent in the later stage to achieve the effect of slow release of oxygen. The specific process is as follows: riboflavin forms RB* under ultraviolet light, RB* reacts with O2, the electrons released by RB* convert O2 into singlet oxygen 1O2, peroxide (H2O2) loses electrons as an electron donor to generate O2, RB* obtains electrons and returns to the ground state RB, 1O2 oxidizes tyrosine into tyrosine residues, and the two tyrosine residues react and combine to form a dityrosine bond, which is cross-linked between the silk fibroin macromolecules. The overall preparation time is generally about ten minutes, and the efficiency is very high. Therefore, the preparation time of the present invention is short and the production efficiency is high.

[0019] 3. In the preparation method and hydrogel of a photocurable oxygen-generating silk fibroin hydrogel of the present invention, the prepared hydrogel not only has good adhesion and wet mechanical properties (high resilience, compressed to 70%, or even 80% will not break), but also can adjust the composition ratio of the raw materials so that the prepared hydrogel has different mechanical strength and viscoelasticity to meet the needs of different medical environments, wherein the adhesion can make the hydrogel closely attached to the surface of the skin or other tissues, not easy to shift or fall off during use, which is conducive to the therapeutic effect of the loaded peroxide releasing oxygen, so as to achieve continuous oxygen supply to the injured treatment part, and the good wet mechanical properties can make the hydrogel still able to maintain structural stability in a humid environment, maintain the functionality of its dressing, even if some injured parts are active during the treatment process, the good wet mechanical properties can ensure that the hydrogel will not break. Therefore, the present invention not only has good adhesion, but also has strong wet mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a preparation flow chart of the present invention.

[0021] Figure 2 It is an electron microscope scanning image of the hydrogel in the present invention.

[0022] Figure 3 It is another electron microscope scanning image of the hydrogel in the present invention.

[0023] Figure 4 It is a schematic diagram of the stress-strain curve of the hydrogel corresponding to different silk fibroin concentrations in the present invention.

[0024] Figure 5 Schematic diagram of oxygen release effect comparison of the hydrogel in the present invention, wherein the blank group is water.

[0025] Figure 6 It is a before and after comparison diagram of the suspension of the present invention under ultraviolet light irradiation. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0027] See also Figure 1 — Figure 6 , a method for preparing a light-cured oxygen-generating silk fibroin hydrogel, the preparation method comprising the following steps: The first step: firstly, adding the riboflavin solution into the silk fibroin solution and stirring to obtain a mixed solution, and then adding peroxide into the mixed solution and stirring at a constant temperature to obtain a suspension; Step 2: first place the suspension in a light-transmitting mold, and then irradiate the suspension in the mold with ultraviolet light. When the suspension changes from clear to translucent gel, light-cured oxygen-generating silk fibroin hydrogel can be obtained.

[0028] In the second step, the ultraviolet lamp irradiation time is 1-30 minutes.

[0029] In the first step, the mass percentage concentration of the silk fibroin solution is 2%-8%, the concentration of the riboflavin solution is 0.01-0.5 mM / L, and the volume ratio between the silk fibroin solution and the riboflavin solution is 100:1-50:1.

[0030] In the first step, the mass of the peroxide is 0.3%-3.0% of the mass of the mixed solution.

[0031] The peroxide is benzoyl peroxide, calcium peroxide or any mixture of the two.

[0032] In the first step, the constant temperature stirring means that after adding peroxide to the mixed solution, constant temperature stirring is performed under a magnetic heating stirrer at a temperature of 25-70° C. for 5-35 minutes.

[0033] In the first step, the silk fibroin solution is prepared according to the following steps: First, degummed silk is obtained, cut into pieces, and then placed in a lithium bromide solution, and then dissolved in a water bath at a temperature of 20-65°C, and then dialyzed for 48-72 hours, and then centrifuged to obtain a silk fibroin solution; The concentration of the lithium bromide solution is 5-15 mol / L, and the mass volume ratio of the degummed silk to the lithium bromide solution is 1:2kg-1:10L.

[0034] The degummed silk is prepared according to the following steps: First, the raw silk is placed in a container containing deionized water, and anhydrous sodium carbonate is added for the first time, and then heated while stirring until boiling for 15-45 minutes, then the silk is taken out for washing, and then the washed silk is added to a container containing deionized water, and anhydrous sodium carbonate is added for the second time, and then heated while stirring until boiling for 15-45 minutes, then the silk is taken out for washing, and then the washed silk is added to a container containing deionized water, and anhydrous sodium carbonate is added for the third time, and then heated while stirring until boiling for 15-45 minutes, then the silk is taken out for washing, and then dried to obtain degummed silk; The mass of anhydrous sodium carbonate added for the first and second times is greater than the mass of anhydrous sodium carbonate added for the third time.

[0035] During the first, second and third stirring and heating, the mass ratio of silk to deionized water was in the range of 1:10-1:100 each time. Meanwhile, after adding anhydrous sodium carbonate each time, the mass percentage concentration of sodium carbonate was in the range of 0.01-0.5%.

[0036] A hydrogel is prepared according to the preparation method of the light-cured oxygen-generating silk fibroin hydrogel.

[0037] The supplementary technical features of the present invention are as follows: In the present invention, the water bath heating temperature is 20-65°C, preferably the heating time is 0.5-2h, more preferably the heating temperature is 50°C, and the dissolution time is 30min.

[0038] The preferred drying temperature of the silk after cleaning in the present invention is 50-80°C. The reason is that it can prevent the drying efficiency from being too slow due to too low a temperature, and can also allow the degummed silk to dry slowly, preventing the surface of the silk from being damaged by high-temperature drying. On this basis, it is further preferred to dry at 60°C.

[0039] The reason why the mass of anhydrous sodium carbonate added for the first and second times is limited to be greater than the mass of anhydrous sodium carbonate added for the third time in the present invention is that the addition of anhydrous sodium carbonate needs to be reduced for the third time in order to prevent the silk from losing a large amount of silk raw materials during silk degumming.

[0040] The reason why the concentration of lithium bromide solution in the present invention is limited to 5-15 mol / L is that if the concentration of lithium bromide solution is too low, the silk dissolution rate will be too slow, and if the concentration is too high, the dialysis time will be too long.

[0041] The reason why the mass volume ratio of degummed silk to lithium bromide solution is limited to 1:2kg-1:10L in the present invention is that if the concentration of lithium bromide solution is too low, the silk dissolution rate will be too slow, while if the concentration is too high, the dialysis time will be too long.

[0042] The reason why the mass of peroxide in the present invention is limited to 0.3%-3.0% of the mass of the mixed solution is that too low or too high a peroxide dosage will result in a poor gelling effect, while too low a peroxide dosage will also result in a small amount of oxygen release.

[0043] The reason why the concentration of riboflavin solution in the present invention is limited to 0.01-0.5 mM / L is that it will lead to poor gel effect, because riboflavin, as a photoinitiator, promotes the conversion of tyrosine to dityrosine. If the concentration is further increased, the gel will reach the top and will no longer promote the conversion rate, resulting in waste.

[0044] Embodiment 1: See also Figure 1, a method for preparing a light-cured oxygen-generating silk fibroin hydrogel, comprising the following steps: S1. First, place the raw silk in a container containing deionized water, the mass ratio of deionized water to silk is 50:1, and add anhydrous sodium carbonate for the first time, the mass percentage concentration of sodium carbonate after addition is 0.1%, then stir and heat until boiling for 30 minutes, then take out the silk to wash, then add the washed silk to a container containing deionized water, and add anhydrous sodium carbonate for the second time, the amount of deionized water and sodium carbonate is the same as the first time, then stir and heat until boiling for 30 minutes, then take out the silk to wash, then add the washed silk to a container containing deionized water, the amount of deionized water is the same as the first time, and add anhydrous sodium carbonate for the third time, the mass percentage concentration of sodium carbonate after addition is 0.05%, then stir and heat until boiling for 30 minutes, then take out the silk to wash, and then dry it at 60°C to obtain degummed silk; S2, first take out the degummed silk from step S1, then place it on a tray balance for quantitative weighing, then cut it into pieces and place it in a conical flask containing lithium bromide solution, the concentration of the lithium bromide solution is 9.3 mol / L, the mass volume ratio of the degummed silk to the lithium bromide solution is 1:50 (m / v), then dissolve it in a water bath at 50°C for 30 min, and after it is completely dissolved, dialyze it for 3 days, then centrifuge and filter it to obtain a silk fibroin solution with a mass percentage concentration of 4%; S3, adding the riboflavin solution to the silk fibroin solution and stirring to obtain a mixed solution, wherein the concentration of the riboflavin solution is 0.1 mM / L, and the volume ratio of the riboflavin solution to the silk fibroin solution is 1:100, and then adding calcium peroxide to the mixed solution and stirring at a constant temperature, wherein the mass of the peroxide is 1.0% of the mass of the mixed solution, to obtain a suspension; S4. Take out the suspension first, pour it into the membrane (i.e., the orifice plate), and then irradiate it under ultraviolet light for 5 minutes. Observe that the suspension changes from clear to translucent gel (such as Figure 6 As shown, the upper row in the figure is the state before irradiation, and the lower row is the state of forming a hydrogel after irradiation), so as to obtain a light-cured oxygen-generating silk fibroin hydrogel.

[0045] A hydrogel is prepared according to the preparation method of the light-cured oxygen-generating silk fibroin hydrogel.

[0046] like Figure 2 , Figure 3 As shown, electron microscopy scanning of the obtained light-cured oxygen-generating silk fibroin hydrogel clearly shows that peroxide ( Figure 2 The area circled in red. Figure 3The blue circle (in the middle) is evenly mixed in the silk fibroin hydrogel and gradually exposed to the outside as the hydrogel degrades under the action of the tissue fluid at the wound site, gradually releasing oxygen.

[0047] like Figure 4 As shown, the prepared light-cured oxygen-generating silk fibroin hydrogel has high physical strength, good resilience and toughness, strong viscoelasticity (it can be compressed to 80% on the horizontal axis, and can return to its original appearance after the external force is withdrawn, with good elastic recovery, and the hydrogel contains a large amount of water, which will flow under long-term stress and has viscous properties). It will not be broken until it is compressed to 70% or even 80%, which meets the needs of wound dressing.

[0048] like Figure 5 As shown, the prepared light-cured oxygen-producing silk fibroin hydrogel can continuously release oxygen within a week. On the first day, it releases a large amount of oxygen to improve the hypoxia of the injured area in the early stage. In the later stage, it can maintain a certain level of continuous oxygen release to maintain the local oxygen concentration in the wound, promote angiogenesis and collagen synthesis, thereby accelerating wound healing, while inhibiting the formation of scar tissue and reducing scar formation.

[0049] Embodiment 2: The basic content is the same as that of Example 1, except that: In step S1, silk cleaning means: firstly, the taken silk is placed in clean water for cleaning and kneading, and then the same operation is repeated once after kneading, and then the silk is placed in deionized water for cleaning and kneading for the third time. So far, a total of three cleanings are performed.

[0050] The above description is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiment. Any equivalent modifications or changes made by ordinary technicians in this field based on the contents disclosed by the present invention should be included in the protection scope recorded in the claims.

Claims

1. A method for preparing a light-cured oxygen-generating silk fibroin hydrogel, characterized in that: The preparation method comprises the following steps: The first step: firstly, adding the riboflavin solution into the silk fibroin solution and stirring to obtain a mixed solution, and then adding peroxide into the mixed solution and stirring at a constant temperature to obtain a suspension; Step 2: first place the suspension in a light-transmitting mold, and then irradiate the suspension in the mold with ultraviolet light. When the suspension changes from clear to translucent gel, light-cured oxygen-generating silk fibroin hydrogel can be obtained.

2. The method for preparing a light-cured oxygen-generating silk fibroin hydrogel according to claim 1, characterized in that: In the second step, the ultraviolet lamp irradiation time is 1-30 minutes.

3. The method for preparing a light-cured oxygen-generating silk fibroin hydrogel according to claim 1 or 2, characterized in that: In the first step, the mass percentage concentration of the silk fibroin solution is 2%-8%, the concentration of the riboflavin solution is 0.01-0.5 mM / L, and the volume ratio between the silk fibroin solution and the riboflavin solution is 100:1-50:

1.

4. The method for preparing a light-cured oxygen-generating silk fibroin hydrogel according to claim 1 or 2, characterized in that: In the first step, the mass of the peroxide is 0.3%-3.0% of the mass of the mixed solution.

5. The method for preparing a light-cured oxygen-generating silk fibroin hydrogel according to claim 4, characterized in that: The peroxide is benzoyl peroxide, calcium peroxide or any mixture of the two.

6. The method for preparing a light-cured oxygen-generating silk fibroin hydrogel according to claim 1 or 2, characterized in that: In the first step, the constant temperature stirring means that after adding peroxide to the mixed solution, constant temperature stirring is performed under a magnetic heating stirrer at a temperature of 25-70° C. for 5-35 minutes.

7. The method for preparing a light-cured oxygen-generating silk fibroin hydrogel according to claim 1 or 2, characterized in that: In the first step, the silk fibroin solution is prepared according to the following steps: First, degummed silk is obtained, cut into pieces, and then placed in a lithium bromide solution, and then dissolved in a water bath at a temperature of 20-65°C, and then dialyzed for 48-72 hours, and then centrifuged to obtain a silk fibroin solution; The concentration of the lithium bromide solution is 5-15 mol / L, and the mass volume ratio of the degummed silk to the lithium bromide solution is 1:2kg-1:10L.

8. The method for preparing a light-cured oxygen-generating silk fibroin hydrogel according to claim 7, characterized in that: The degummed silk is prepared according to the following steps: First, the raw silk is placed in a container containing deionized water, and anhydrous sodium carbonate is added for the first time, and then heated while stirring until boiling for 15-45 minutes, then the silk is taken out for washing, and then the washed silk is added to a container containing deionized water, and anhydrous sodium carbonate is added for the second time, and then heated while stirring until boiling for 15-45 minutes, then the silk is taken out for washing, and then the washed silk is added to a container containing deionized water, and anhydrous sodium carbonate is added for the third time, and then heated while stirring until boiling for 15-45 minutes, then the silk is taken out for washing, and then dried to obtain degummed silk; The mass of anhydrous sodium carbonate added for the first and second times is greater than the mass of anhydrous sodium carbonate added for the third time.

9. The method for preparing a light-cured oxygen-generating silk fibroin hydrogel according to claim 8, characterized in that: During the first, second and third stirring and heating, the mass ratio of silk to deionized water was in the range of 1:10-1:100 each time. Meanwhile, after adding anhydrous sodium carbonate each time, the mass percentage concentration of sodium carbonate was in the range of 0.01-0.5%.

10. A hydrogel, characterized in that: The hydrogel is prepared according to the method for preparing a light-cured oxygen-generating silk fibroin hydrogel according to claim 1 or 2.

Citation Information

Patent Citations

  • Oxygen sustained-release hydrogel and preparation method and application thereof

    CN115887780B

  • Preparation method and application of high-strength and high-modulus silk material

    CN114249982A

  • High-elasticity silk fibroin hydrogel as well as photocuring preparation method and application thereof

    CN116041735A

  • High-strength and high-toughness silk fibroin self-reinforced hydrogel and preparation method thereof

    CN118027686A

  • Oxygen-releasing and anti-inflammatory double-layer hydrogel as well as preparation method and application thereof

    CN118286503A